The Swiss Franc Exchange Rate and Deviations from Uncovered Interest Parity: Global vs Domestic Factors - Mathias Hoffmann; Rahel Suter (Swiss Journal of Economics and Statistics, 2010)
We examine the role of global and country-specific factors for the Swiss franc exchange rate in the period 1990–2009. Simple asset pricing theory would predict that exchange rates reflect relative movements in national discount factors and that systematic departures from uncovered interest parity can only be explained by international differences in the exposure to the common (global) component of all national discount factors. We extend the methodology of LUSTIG, ROUSSANOV and VERDELHAN (2009) to allow individual currencies' exposure to this global factor to vary over time as a function of the interest rate differential. This allows us to study the time-varying risk characteristics of individual currency pairs. We find that the Swiss franc acts as a safe haven against some currencies - notably for dollar-based investors - but not for all, specifically not the euro. Also, the extent to which global factors have weighed on the Swiss franc exchange rate has varied over the sample period and appears more subdued in the global low interest rate environment of the last decade.
Keywords: F31; F36; G12; 330; Currency risk; exchange rate; save haven effects; uncovered interest parity (UIP)